2023
DOI: 10.3390/microorganisms11122829
|View full text |Cite
|
Sign up to set email alerts
|

The Salinity Survival Strategy of Chenopodium quinoa: Investigating Microbial Community Shifts and Nitrogen Cycling in Saline Soils

Xuli Zhao,
Tianzhu Meng,
Shenghan Jin
et al.

Abstract: Quinoa is extensively cultivated for its nutritional value, and its exceptional capacity to endure elevated salt levels presents a promising resolution to the agricultural quandaries posed by salinity stress. However, limited research has been dedicated to elucidating the correlation between alterations in the salinity soil microbial community and nitrogen transformations. To scrutinize the underlying mechanisms behind quinoa’s salt tolerance, we assessed the changes in microbial community structure and the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The decline in Verrucomicrobiota in oligohaline sites has also been observed across the Baltic Sea salinity gradient (Herlemann et al., 2011) and demonstrates a possible preference of this phylum for non‐saline environments, although some members have been cultured at seawater salinities (Schlesner et al., 2006). Myxococcota have been identified as key components of tidal freshwater wetlands elsewhere (Morina & Franklin, 2022), and have been shown to decline with increased salinity (Zhao et al., 2023), in concordance with our results. While we found positive effects of salinity on the relative abundance of Chloroflexi, another common freshwater and estuarine wetland phylum (Huang et al., 2022; Ikenaga et al., 2010), results in other studies have shown mixed responses to low‐level salinity (Zhang et al., 2021; Zhao et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The decline in Verrucomicrobiota in oligohaline sites has also been observed across the Baltic Sea salinity gradient (Herlemann et al., 2011) and demonstrates a possible preference of this phylum for non‐saline environments, although some members have been cultured at seawater salinities (Schlesner et al., 2006). Myxococcota have been identified as key components of tidal freshwater wetlands elsewhere (Morina & Franklin, 2022), and have been shown to decline with increased salinity (Zhao et al., 2023), in concordance with our results. While we found positive effects of salinity on the relative abundance of Chloroflexi, another common freshwater and estuarine wetland phylum (Huang et al., 2022; Ikenaga et al., 2010), results in other studies have shown mixed responses to low‐level salinity (Zhang et al., 2021; Zhao et al., 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The root system has the ability to absorb and transport water, nutrients, and mineral elements [ 15 , 16 ]. The root morphological indices of quinoa seedlings under different treatments are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%